Evaluation of the consumption of medicines for the treatment of obesity: a study conducted in pharmacy of Teresina-Piauí municipality (Research, Society and Development, 2020)
Obesity is a disease considered as a global epidemic. In Brazil, obesity been increasing in all age groups without distinction of sex. Together with obesity another concern arises, the indiscriminate and abusive use of medications for the treatment of this patology. The aim of this article was to identify wich drugs for the treatment of obesity are most for the treatment of this pathology consumed in the Teresina city. It was observed that the most commercialized drug for treatment obesity is Sibutramine, followed by Orlistate, Fluoxetine, Duloxitin and Topiramate. Remembering that the last three are off label medications(outside the leaflet) i.e. are marketed for the treatment of anxiety and depression. The highest service was for female users, between 20 to 29 years old. It was observed in the study that some users do not always make the correct use of the medicines, and, the influences of third parties are part of the processes seduced by advertising of the pharmaceutical industries.